The THE INFLUENCE OF SPECIAL AUTONOMY FUNDS ON THE POVERTY RATE IN BIAK PAPUA - Sigalingging, Andy Sahat Maasi; Wijaya, Natasya (Gema Kampus IISIP YAPIS Biak, 2025)
This study analyzes the relationship between special autonomy funds (independent variable) and the poverty rate. (variabel dependen). The results show that special autonomy funds do not significantly affect the poverty rate in Biak, Papua. The results also indicate that this study has a significant impact on the study's outcomes, suggesting that this study may be useful in understanding other factors influencing poverty in Biak. These findings suggest that special autonomy funds may not be a significant factor in influencing poverty in Biak, Papua. The special autonomy funds used in Papua often face implementation challenges on the ground, especially in the context of Papua. Biak also emphasizes that special autonomy funds often encounter implementation challenges in the field, particularly in the context of Papua, where structural issues such as economic and geographical disparities remain dominant. The R² value of 0.039 indicates that only 3.9% of the variation in poverty levels can be explained by the variation in special autonomy funds. Special autonomy funds often depend on various multidimensional factors, which include access to education, healthcare services, economic infrastructure, and local capacity development. The special autonomy funds used in Papua may not have been optimally focused.